Avaliação da segurança reprodutiva e da transmissão passiva de imunidade após processo de imunização com proteína peroxidoxina recombinante de Leishmania braziliensis durante a prenhez de ratas - Ana Paula Barcelos Reinaque (2015)
The peroxidoxin recombinant protein of Leishmania braziliensis associated with adjuvant MPL (Monophosphoryl Lipid A) has been shown to be a promising candidate for antileishmaniose vaccine. Although the immunogenic potential of the vaccine process is extensively shown for different anti-parasitic vaccines, data on the safety assessment of recombinant proteins in vaccine formulations administered during pregnancy, as well as information about the passive transfer of immunity in animals vaccinated during pregnancy are remain scarce. The objective of this study was to evaluate vaccine safety when the administration during pregnancy, with possible causes of maternal or fetal losses and evaluate the passive transfer of immunity to the newborn after immunization process in experimental model with Wistar rats. Rats in reproductive age were mated and allocated in three groups: Control - rats received saline; Adjuvant - rats received adjuvant MPL, and Vaccine - rats that received the composition adjuvant and peroxidoxin. The administration was by subcutaneous injection at the dorsal region, three times (days zero, seven and 14 of pregnancy). At day 21 of pregnancy the animals were anesthetized and blood collected for serological analysis by ELISA. There was an increase in post-implantation loss in the vaccine group (14.7%) compared to the control group (5.0%) and adjuvant (4.4%). It was verified a higher rate of visceral anomalies in fetuses from the vaccine group. Concerning to serology, it was found that levels of anti- peroxidoxin IgG were higher in the vaccine group. Offspring of vaccinated rats also showed higher IgG levels compared the offspring of rats control and adjuvant. The anti-IgG peroxidoxina transfer remains in the postnatal period, via breastfeeding, and transfer rates of antibodies through the placenta or breast-feeding are similar. These data showed that the immunization stimulated the production of IgG anti-peroxidoxin immunoglobulin, and this immunization transferred to the fetus through the placenta and milk, but the vaccine increased post-implantation loss and fetal anomalies, showing that its use during pregnancy requires care and further study.